(untitled) (Revista Educação, Artes e Inclusão, 2023)
The article presents a bibliometric survey of the content of the Magazine Education, Arts e Inclusion, and encompasses a period that corresponds to the first edition, published in 2008, until the last edition, published in 2022, in a total of 432 published articles. 59 texts on the theme Education, Arts and Inclusion of people with disabilities and related themes are part of the analysis, that is, only 13.6% of the analyzed publications fit the theme highlighted in the title of the own magazine. The main results pointed out by the analyzes is the production of articles with an emphasis on the Visual Arts. One fact that also called our attention, corroborating with other texts on the area of ​​knowledge, is that 75.83% of authors on this topic are women. The themes of the productions focus on the discussion of inclusion in and through Art. The objectives of the works deal with the importance of understanding its role in school inclusion, but there are also records, in smaller numbers, related to social inclusion through Art of people with disabilities.